Pengembangan Strategi Efektif untuk Menyeimbangkan Tuntutan Akademik dan Profesional bagi Mahasiswa - Fathorrahman Fathorrahman; Intan Purnama Sari; Reva Aliya Nabila; Muhammad Alwan (Jurnal PKM Manajemen Bisnis, 2026)
This Community Service Program (PKM) focuses on developing effective strategies to help students balance academic and professional demands, particularly in preparation for continuing their education while working after graduation. The activity was motivated by the increasing need for high school students to understand self-readiness, time management, and adaptability as they transition into higher education and employment. The main objective of the program was to enhance students’ knowledge, skills, and confidence in managing dual roles as workers and university students. The PKM was conducted at SMK Perguruan Rakyat 1 Jakarta on 31 October 2025, involving 16 lecturers and students from Universitas Pamulang as facilitators and 50 twelfth-grade students as participants. The implementation consisted of three stages: preparation, execution, and reporting. The execution phase included material presentation, hands-on practice, group discussions, and question-and-answer sessions designed to encourage active participation and reflection. The results show that students gained a clearer understanding of the challenges and strategies required to balance work and study, demonstrated increased motivation, and expressed positive responses toward the practical guidance provided. Overall, the program effectively supported students’ readiness to pursue higher education while entering the workforce.